A STUDY ON THE ABILITY OF THE FIRST GRADE STUDENTS OF SMK DAREL HIKMAH PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is intended to describe a descriptive study which is tofind out the ability of the first-grade students of SMK Darel Hikmah Pekanbaru in comprehending Descriptive Texts. This is quantitative investigation, the subject ofthis investigation was the first-grade students of SMK Darel Hikmah Pekanbaru which consisted of 33 students. The data collection method used is a descriptive method by giving tests to students using a google form which contains multiple choices consisting of 40 questions. Based on the data analysis eight components of reading comprehension and descriptive texts like finding the most idea, finding factual information, finding references, finding inference, finding the generic structure of descriptive texts, finding social information of descriptive texts, and finding language features of descriptive text, it absolutely was found that score of the students is in finding references with the main score of 75.6 which is categorized as a good level. While the lowest score of the students is to finding language features of descriptive texts with the mean score of 58.8. The conclusion of this research shows that the first grade students of SMK Darel Hikmah Pekanbaru in Comprehending Descriptive texts have a good level of understanding, with a mean score of 68.7.Key Words:Students’Ability,Comprehending,DescriptiveText